An Analytical Scrutiny with Fuzzy Approach on CGMA' Business Model Ontology - Mojtaba Ghanbarzadeh (International Journal of Management, Accounting and Economics, 2022)
Business model is one of the available structures of organizational management for developing competitive advantage. The purpose of this study is an analytical scrutiny with fuzzy approach on the Chartered Global Management Accountant (CGMA)' business model ontology. To study the cause-and-effect relationships and prioritize the dimensions and components of the proposed framework, fuzzy DNAP method (combination of DEMATEL and Analytic Network Process (ANP) in a fuzzy environment) has used. A pairwise questionnaire of dimensions and components dispatch among 13 experts aware of management accounting and business models issues. The experts were selected using the judgmental and purposeful sampling method. The results show that the dimensions of value delivery, value capture, value creation and value definition ranked first to fourth, respectively. The value definition dimension also has a greater impact than other dimensions and the value delivery dimension has a greater impact intensity. In the general evaluation, it was found that the component “Explaining how to use technology in presenting the created values” and the component of “Determining the value propositions” are of the highest and lowest level, respectively. According to the research findings, Management accountants, as consultants and business partners, should be on the ontology of the business model of the Chartered Global Management Accountant (CGMA) in order to provide better guidance to management, emphasis and pay more attention to priority dimensions and components.